(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Generally, the biosphere is undergoing greater weather excesses, variations in rainfall patterns, heat, and cold waves, as well as growing droughts and floods. These phenomena have undesirable effects on the surroundings and on people’s lives and occupations. Side-lined groups and societies in the poorest counties of the world are predominantly impacted, even as they are least accountable for these variations (United Nations Development Programme (UNDP, 2009).